1998
DOI: 10.1046/j.1365-2222.1998.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid reduced lamina reticularis of the basement membrane by modulation of insulin‐like growth factor (IGF)‐I expression in bronchial asthma

Abstract: These results suggest that corticosteroid treatment in asthma can reduce the lamina reticular thickness by modulation of IGF-I expression with consequent inhibition of the airway infiltration by inflammatory cells, and therefore may help to prevent remodelling of the airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 51 publications
5
82
1
3
Order By: Relevance
“…The findings from these studies also suggest that the degree of fibrosis is related to AHR, consistent with past studies [30][31][32] that have shown that in addition to collagen IV being increased in the subepithelial layer various interstitial collagens are also synthesized and deposited into areas surrounding the subepithelial and within interstitial regions of the airway in human asthma. This increase in aberrant collagen deposition increases total wall thickness of the airway, resulting in a reduction in the diameter of the airway lumen.…”
Section: Discussionsupporting
confidence: 79%
“…The findings from these studies also suggest that the degree of fibrosis is related to AHR, consistent with past studies [30][31][32] that have shown that in addition to collagen IV being increased in the subepithelial layer various interstitial collagens are also synthesized and deposited into areas surrounding the subepithelial and within interstitial regions of the airway in human asthma. This increase in aberrant collagen deposition increases total wall thickness of the airway, resulting in a reduction in the diameter of the airway lumen.…”
Section: Discussionsupporting
confidence: 79%
“…In one study of 10 patients with severe asthma, despite longterm corticosteroid treatment (mean 3.7 yrs), the asthmatic subjects showed thickening of basement membrane reticular collagen comparable to controls without asthma [46]. In contrast, in 24 patients with asthma, 6 months of treatment with inhaled beclomethasone dipropionate, compared to placebo, decreased the number of activated eosinophils, T-cells and fibroblasts and the thickness of the lamina reticularis in biopsy samples from the bronchial mucosa [47]. In another bronchial bioptic study of 14 patients with asthma, 3 months of budesonide treatment (compared to baseline) reduced the number of infiltrating eosinophils and lymphocytes and improved the structure of the bronchial epithelium [48].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I is a potent mitogen and stimulant of collagen secretion in fibroblasts (2), and has been implicated in the pathogenesis of fibrosis in a number of lung disorders (3)(4)(5). IGF-I is up-regulated in the airways of mice after allergen challenge (6), and IGF-I levels in biopsies of patients with asthma correlate with subepithelial fibrosis (7). The regulation of IGF-I is mediated, in part, by a system of six IGFBPs (8).…”
mentioning
confidence: 99%